Substance and Subject, from Kant to Hegel - Klotz, Christian (Studia Kantiana, 2023)
In the Preface of the Phenomenology o Spirit, Hegel famously claims that "everything turns on grasping and expressing the True, not only as Substance, but equally as Subject". This article aims to put Hegel's claim into the context of the preceding discussion about the relation between the concepts of subject and substance in Kant and Fichte. Whereas Kant adopted a concept of subject which goes together with agnosticism regarding the question if subjects are substances, Fichte transformed the concept of subject into a concept which signifies a peculiar ontological status, that is, a mode of being which is characterized by the self-positing nature which distinguishes subjects from things. At the same time, Fichte understands the concept of substance as being subordinated to that of subject. It is the central thesis of the article that the Hegelian claim presupposes the Fichtean ontologicalization of the concept of subject. However, it is also argued that Hegel, in contrast to Fichte, construes the concepts of subject and of substance as being equally original.